Characterization of Minerals, Metals, and Materials 2015 - Carpenter, John; Bai, Chengguang; Pablo Escobedo-Diaz, J.; Hwang, Jiann-Yang; Ikhmayies, Shadia; Li, Bowen; Li, Jian; Neves Monteiro, Sergio; Peng, Zhiwei; Zhang, Mingming (The Minerals, Metals & Materials Series,, 2016)
This collection focuses on the characterization of minerals, metals, and materials as well as the application of characterization results on the processing of these materials. Papers cover topics such as clays, ceramics, composites, ferrous metals, non-ferrous metals, minerals, electronic materials, magnetic materials, environmental materials, advanced materials, and soft materials. In addition, papers covering materials extraction, materials processing, corrosion, welding, solidification, and method development are included. This book provides a current snapshot of characterization in materials science and its role in validating, informing, and driving current theories in the field of materials science. This volume will serve the dual purpose of furnishing a broad introduction of the field to novices while simultaneously serving to keep subject matter experts up-to-date.